Development of an Entrepreneurship-Based Entrepreneurship Game for Kids to Instill Entrepreneurial Values in Group B Children at Muslimat NU Kindergarten 14 Nurul Huda Karangduren Pakisaji Malang Regency - Shinta Kirana; Ayu Asmah; Sarah Emmanuel Haryono (Journal of Creative Power and Ambition (JCPA), 2026)
Young children are accustomed to interacting with various gaming applications in their daily lives. This condition presents a challenge for educators to effectively utilize digital media to support learning, particularly in entrepreneurship education. Therefore, there is a need for an Android-based application that can instill entrepreneurial values ​​through engaging and enjoyable gameplay. The purpose of this study was to determine the feasibility of the Entrepreneur for Kids game as an entrepreneurship-based learning medium for fostering entrepreneurial values ​​among Group B children at TK Muslimat NU 14 Nurul Huda Karangduren, Pakisaji District, Malang Regency. This study employed a Research and Development (R&D) approach using the Dick and Carey instructional design model. Data were collected through questionnaires, observations, and documentation. The feasibility of the product was evaluated by subject matter experts and media experts, followed by individual trials and field testing involving 13 Group B children aged 5–6 years. The validation results showed a score of 96.4% from the subject matter experts and 95.2% from the media experts. Meanwhile, the individual trials achieved a score of 90%, and the field testing reached 91.6%. All evaluation results were classified as highly feasible. Therefore, the Entrepreneur for Kids game was deemed suitable for use as a learning medium to foster entrepreneurial values ​​in early childhood education.